Constructing quality-adjusted price indices: a comparison of hedonic and discrete choice models - Nicole Jonker (European Central Bank (ECB), 2002)
The Boskin report (1996) concluded that the US consumer price index (CPI) overestimated the inflation by 1.1 percentage points. This was due to several measurement errors in the CPI. One of them is called quality change bias. We compare two methods in this paper which can be used to correct for quality change bias, namely the hedonic method and a method based on the use of discrete choice models. We compare the underlying micro-economic models of the two methods as well as their empirical implementation. Although the discrete choice model has not been used often to calculate quality-adjusted price indices, past research shows that it might be beneficial to do so.
Keywords: C43; D11; D21; C25; 330